KONSEP INTERIOR RUANG FISIOTERAPI ANAK BERKEBUTUHAN KHUSUS PADA KLINIK ANAK USIA 1-5 TAHUN - Fakhrisa Nur Paramarta (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
Therapy for children with special needs is very important as well as the concept of the room will greatly affect the results. The growth and development clinic in Bandung has very good facilities, but because of awareness of the therapy and its treatment, there are also new methods and facilities for its therapy. Most of the clinics lack the concept of a good therapy room, often only putting all facilities in one room without taking care of existing objects. This research will discuss about the physiotherapy room and how a room can be comfortable and develop a focus on children. This writing process method is a qualitative method, which the author got from an interview with a doctor and a mother who has a child with special needs aged three years, the author also conducted a survey to one of the clinics called the Kinder Clinic in Holis Permai VII Complex. One on one therapy in a room measuring 3x4.7 M2 and a literature study on how to form a comfortable room for children, therapists and parents. The benefit of this research is that it can be seen as an example of a design concept or other redesign concept. The final result of this research is a change in concept due to the many ornaments and others.